2017
DOI: 10.1103/physrevb.95.174428
|View full text |Cite
|
Sign up to set email alerts
|

Signature of Hanle precession in trilayer MoS2 : Theory and experiment

Abstract: Valley-spin coupling in transition-metal dichalcogenides (TMDs) can result in unusual spin transport behaviors under an external magnetic field. Nonlocal resistance measured from 2D materials such as TMDs via electrical Hanle experiments are predicted to exhibit nontrivial features, compared with results from conventional materials due to the presence of intervalley scattering as well as a strong internal spin-orbit field. Here, for the first time, we report the all-electrical injection and non-local detection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Electronic and spin transport [82][83][84][85] in TMDCs is becoming an important topic. It has been shown that the carrier mobility increases with the number of TMDC layers 69,84 , due to reduced Coulomb scattering in thicker samples 86 , while phonon scattering limits the room temperature mobility 85 .…”
Section: Introductionmentioning
confidence: 99%
“…Electronic and spin transport [82][83][84][85] in TMDCs is becoming an important topic. It has been shown that the carrier mobility increases with the number of TMDC layers 69,84 , due to reduced Coulomb scattering in thicker samples 86 , while phonon scattering limits the room temperature mobility 85 .…”
Section: Introductionmentioning
confidence: 99%